Transcriptome and iTRAQ-Based Proteome Reveal the Molecular Mechanism of Intestinal Injury Induced by Weaning Ewe's Milk in Lambs - Han, Lulu; Tao, Hui; Kang, Lingyun; Wang, Shuo; Diao, Qiyu; Han, Deping; Cui, Kai (Frontiers in Veterinary Science, 2022)
Early feeding regime has a substantial lifelong effect on lambs, and weaning ewe’s milk can lead to the intestine injury of lambs. To explore the molecular regulatory mechanism of intestinal injury of lambs under weaning stress, the jejunum was conducted transcriptome and then integrated analyzed with our previous proteome data. A total of 255 upregulated genes and 285 down-regulated genes were significantly identified. These genes showed low overlapping with differentially expressed proteins identified by iTRAQ. However, according to their functions, the differentially expressed genes and proteins with the same expression trend were enriched for similar GO terms and KEGG pathways, such as intestinal lipid absorption, urea cycle, PPAR signaling pathway, and ferroptosis. Furthermore, DEGs, including FABP2, ACSL3, APOA2, APOC3, and PCK1, might play essential roles in intestinal lipid absorption and immune response through the PPAR signaling pathway and ferroptosis. This study could provide new insights into early lamb breeding at the molecular level.in